2023
DOI: 10.5070/g601197
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic violations affect social inferences about the speaker

Abstract: Listeners systematically extract two types of information from linguistic utterances: information about the world, and information about the speaker – i.e., their social background and personality. While both varieties of content have been widely investigated across different approaches to the study of language, research in pragmatics has mostly focused on the former kind. Here we ask how listeners reason about a speaker’s conversational choices to form an impression about their personality. In three experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…In a recent study, Beltrama and Papafragou (2023) also demonstrated social generalizations at the individual level. In their study, speakers who violated pragmatic expectations by being underinformative or irrelevant were rated as less “warm” (e.g., friendly and considerate) and less “competent” (e.g., knowledgeable) than speakers who were informative and relevant.…”
Section: Discussionmentioning
confidence: 87%
“…In a recent study, Beltrama and Papafragou (2023) also demonstrated social generalizations at the individual level. In their study, speakers who violated pragmatic expectations by being underinformative or irrelevant were rated as less “warm” (e.g., friendly and considerate) and less “competent” (e.g., knowledgeable) than speakers who were informative and relevant.…”
Section: Discussionmentioning
confidence: 87%
“…Against this background, our study investigated whether general age-related differences in prosocial linguistic behavior would emerge at different stages of adult development, and whether these differences would vary as a function of contextual manipulations critical to everyday life (i.e., whether the recipient was directly affected by the bad news, whether the bad news was severe, and whether the bad news was health-related). In turn, our findings shed light on which contextual cues younger and older adults are more sensitive to when formulating their utterances, and to what degree their use of prosocial speech acts is pragmatically appropriate (i.e., used in contexts in which a social goal could be achieved), which is highly relevant for the development and maintenance of interpersonal relationships (Beltrama et al, 2023; Holtgraves & Bonnefon, 2017; Lubben & Gironda, 2003).…”
Section: A Lifespan Approach To Prosocial Speech Actsmentioning
confidence: 87%